Overpopulation - William A. Jackson (Encyclopedia of Global Studies, 2012)
This article discusses the concept of overpopulation and its practical relevance. Definitions of overpopulation are considered, including approaches centred on sustainability and on average or total welfare. Overpopulation has been linked to the wish for national population policies, which raise various ethical matters and coordination problems at the international level. Long-standing debates have arisen over Malthusianism and the differing views in rich and poor countries towards population control. Any practical applications of overpopulation have always proved difficult and controversial.
https://doi.org/10.4135/9781452218557
Keywords: J10; J18; Q56; 330; sustainability; optimum population; Malthusianism; demographic transition; population policies